Re-analysis of a human hepatitis B virus (HBV) isolate from an East African wild born Pan troglodytes schweinfurthii: evidence for interspecies recombination between HBV infecting chimpanzee and human. - Magiorkinis, E; Magiorkinis, G; Paraskevis, D; Hatzakis, A (2005)
According to current estimates, hepatitis B virus (HBV) has infected 2 billion people worldwide and among them, 360 million suffer from chronic HBV infection. Except humans, HBV or HBV-like viruses have also been isolated from different species of apes and mammals. Although recombination has been described to occur extensively between different genotypes within the human HBV lineage, no recombination event has ever been reported between human and non-human primate HBV sequences. It was our objective to perform an exhaustive search for recombination between human and non-human primate HBV strains among all available full-length human and non-human primate HBV sequences, using bootscanning and phylogenetic analyses. Intriguingly, we found that an HBV sequence isolated from a wild born Pan troglodytes schweinfurthii in East Africa-FG-is a recombinant consisting of HBV infecting chimpanzee (ChHBV) and human genotype C. More specifically, in a fragment of approximately 500 nt (positions 551-1050 spanning half of the RT domain of pol, which overlaps with half of the coding region of the small surface protein), FG grouped with HBV genotype C, while in the rest of the genome it grouped with ChHBV sequences. Phylogenetic analyses showed that in the latter region FG was more closely related to the Pan troglodytes troglodytes subspecies, forming an outlier to this group. Moreover, we show evidence that the recombination event occurred after the initial dispersion of HBV genotype C in humans. Finally, our findings point out that although rare recombination between HBV viruses infecting different species occurs.